Organic production in Ukraine: state and prospects - Славгородська, Ю. В. (Scientific Progress & Innovations, 2016)
The article reviews the current state of organic products in Ukraine. We analyzed the distribution of organic operators for areas of the country. As a result, we considered prospects of development of organic production and feasibility of increasing its scope for increasing demand. We discovered constraints of the development in production of organic products. The measures of stimulation of production of organic products are offered.